The effects of gums as emulsifier on the emulsion stability in cosmetic formulation / Muhammad Zimam Akid Mohd Haniffa - Mohd Haniffa, Muhammad Zimam Akid; Muhammad Azam, Nur Syahirah Najibah; Syed Sulaiman, Sharifah Nurshahirah; Mohd Khamri, Nurul Hidayah
This study analysed the effects of gum as emulsifiers on the emulsion stability in cosmetic formulations that were obtained from several articles. Emulsion-based formulations, where surfactants and emulsifiers play a contrasting but equally important role, are widely used in medicines, food and cosmetics. In order to allow droplet dispersion of one phase at a time, both are able to adsorb at the oil and water interface. In cosmetic and pharmaceutical applications, emulsions are commonly used. The emulsions are lotions, creams and certain ointments, gels, as well as pastes. The type of emulsion produced by either oil-in-water or water-in-oil depends primarily on the polysaccharide used in the emulsification process and the quantity of each step that could affect the stable emulsion forming process. Naturally occurring polymers are currently of primary importance, among which polysaccharides, due to their simple accessibility, eco-friendly and non-toxic nature, occupy superior positions. The called microbial polysaccharide gums have a number of cosmetic functions, including emulsion stabilizer, film former, binder, viscosity-enhancing agent, and skin-conditioning agent. Since emulsions are not thermodynamically stable systems, they can be separated by various physicochemical processes, such as gravitational separation, flocculation and coalescence. The use of stabilizers is therefore required for the formulation of emulsions and for theirlong-term stability. Natural gums are released in tear-like, striated nodules or amorphous lumps from trees and shrubs. Synthetic gums are often taken advantage of by natural gums because they are accepted by clients. A change to a biocompatible oil is appropriate for a cosmetic or pharmaceutical application, but this also causes drastic changes or changes in the stability of the emulsion. The characteristics that have been analysed to measure the stability of the emulsion in gums are particle size, storage state, zeta potential and treatment process. In the result, the stability of the emulsions could be stabilised when particle size is small which lead to decrease in droplet aggregation. Due to the findings, as such, Xanthan Gum is the most stable gum compared to Arabic gum and Guar gum with the droplet size at 2934 nm. Another parameter that is a storage condition that corresponds to one of the variables that increases the stability of the emulsion, which is the size of the droplet emulsion. Emulsion stability is thus achieved as the particle size decreases as the number of days' increases. Zeta potential is an important parameter for stabilising emulsions. The highest value of the zeta potential leads to an increase in the viscosity of the emulsions. Zeta potential value improves more stabilisation of the emulsions by increasing the value of the zeta potential and resulting in high stability of the emulsions.